AVALIAÇÃO INSTITUCIONAL E ELABORAÇÃO DO PLANEJAMENTO, PLANOS E PROJETOS ANUAIS - Maria Luiza de Sousa Pinha; José Camilo dos Santos Filho (Universidade do Oeste Paulista, 2014)
The objective of this study was to analyze the contribution of the results and conclusions of the internal and external assessment for planning the annual activities of the school in the years 2009, 2010 and 2011. To achieve this goal the research adopted a qualitative approach and used as procedure a case study of a public school of basic education of the state system of education of the State of São Paulo. The data, collected through school environment observation, document research and semistructured interview, indicate that the school uses the data of internal and external evaluation for preparing the planning and annual plans, but does so based only on reflection and decision of the management team and teachers and not on the participation of all school community segments.